2022
DOI: 10.3389/fnins.2022.1011016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of two automated audiometry procedures

Abstract: ObjectiveAutomated pure-tone audiometry has been shown to provide similar hearing threshold estimates to conventional audiometry, but lower correlations were reported at high and low frequencies in audiometric tests than those of manual tests, while the correlations were better in the middle frequencies. In this paper, we used the same equipment and different test procedures for automated testing, and compared the results with manual test results.DesignOne hundred subjects aged 18–36 years were randomly divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…In our previous study, we performed a comparison of manual and automated tests under sound-isolation conditions and found that the reliability at 250 Hz and 8,000 Hz was worse than at other frequencies (Liu et al, 2022), however, this phenomenon did not occur in the present group of subjects, which may be related to the use of different headphones. In the previous study, insert headphones were used for automated audiometry and circumaural earphones were used for manual audiometry; in the present study, KUDUwave audiometer were used for both manual-and automated pure-tone audiometry, which eliminates the calibration differences that were introduced by two different devices, and could easily interpret some changes in hearing thresholds.…”
Section: Discussioncontrasting
confidence: 49%
“…In our previous study, we performed a comparison of manual and automated tests under sound-isolation conditions and found that the reliability at 250 Hz and 8,000 Hz was worse than at other frequencies (Liu et al, 2022), however, this phenomenon did not occur in the present group of subjects, which may be related to the use of different headphones. In the previous study, insert headphones were used for automated audiometry and circumaural earphones were used for manual audiometry; in the present study, KUDUwave audiometer were used for both manual-and automated pure-tone audiometry, which eliminates the calibration differences that were introduced by two different devices, and could easily interpret some changes in hearing thresholds.…”
Section: Discussioncontrasting
confidence: 49%
“…Ambient noise monitoring systems embedded in automated audiometric systems are already available in industry that ‘ensure testing compliance’ [ 28 , 29 ]. Unfortunately, no details are available on what exactly the decisions being made by the software are, nor which criteria should be met for these decisions to be made.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of the STOI estimates of VCV intelligibility in the five languages was validated using psychometric estimates from previously conducted experimental subjective tests [15,16] in a 3AFC speech recognition task. The three alternatives followed a maximal opposition criterion: the two wrong alternatives differ from the spoken stimulus in manner, voicing, and place of articulation (for example, ata, ava, ama) (details are reported in: [12,21,22]) and subjects had to select their response among the three alternatives displayed on a touch-sensitive screen.…”
Section: Intelligibility Measuresmentioning
confidence: 99%
“…However, hearing screening at a distance may open new challenges in hearing health care. For example, remote testing using pure-tone audiometry has limitations in terms of output levels calibration and sensitivity to environmental noise [16]. Speech-in-noise testing can help overcome this limitation, but language-specific test stimuli may lead to issues with non-native listeners [17].…”
Section: Introductionmentioning
confidence: 99%